Sharia Cooperative Financial Inclusion and Entrepreneurial Orientation To Improve Sharia-Based MSME Empowerment New Normal Era In Malang City - Raisa Fitri; Murniati, Aniek (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2021)
The problem that is faced by Islamic boarding school-based MSMEs is capital constraints. This capital constraint is due to the lack of information on MSME actors about how to apply for credit and how to utilize financing funds. Financial inclusion can be realized, there is a need for parties who have direct contact with the community, especially the lower middle class in terms of distributing micro credit. Therefore, the role of sharia banking and sharia cooperatives needs to be increased to increase the growth of MSMEs in Malang City, especially Sharia-based MSMEs so that financial inclusion can be realized. Based on the results of a survey conducted through the Cooperatives and MSMEs Offices, there are about 25 Sharia cooperatives with several criteria, namely cooperatives in Malang City that are legal entities. The multiple regression was chosen to be carried out in this research activity. The results of the study show that the good performance of an MSMEs can be seen from its entrepreneurial orientation because the increasing spirit of entrepreneurial orientation will motivate MSMEs to make innovations and be ready to face all possible risks in the future.